2019
DOI: 10.12669/pjms.35.6.115
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of urinary tract infection and antibiotic sensitivity of uropathogens in patients with diabetes

Abstract: Objective:To determine the frequency of urinary tract infections and antibiotic sensitivity among patients with diabetes.Methods:This observational study was carried out in Microbiology Department of Baqai Institute of Diabetology and Endocrinology (BIDE), Baqai Medical University from April 2015 to June 2016. All patients with diabetes having symptoms of UTI attending out patients department of BIDE were analyzed. All samples received in the laboratory were processed according to Clinical and Laboratory Stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
42
3
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 13 publications
19
42
3
7
Order By: Relevance
“…We also determined the antibacterial activity of 3D-printed zein tablets formulated with NA against suspension cultures of Staphylococcus aureus ( Figure 7B). with previous reports [62,63].…”
Section: Biomedical Applications: Drug Releasesupporting
confidence: 92%
“…We also determined the antibacterial activity of 3D-printed zein tablets formulated with NA against suspension cultures of Staphylococcus aureus ( Figure 7B). with previous reports [62,63].…”
Section: Biomedical Applications: Drug Releasesupporting
confidence: 92%
“…This rate is comparable to the rates reported from other studies in Ethiopia (Debre Tabor (10.9%) [20], Hawassa 13.8% [35], Addis Ababa 10.9% [36]), India 12.2% [18] and Romania (10.7%) [37]. However, much higher prevalence rates were reported from Bahir Dar (30.5%) [38], and Arbaminch (33.8%) [39] in Ethiopia, Sudan (19.5%) [40], India (22%) [21], Pakistan (52.76%) (41)], Egypt (52.2%) [19], and Nepal (54.25%) [42]. Inclusion of asymptomatic DM patients and exclusion of catheterized DM patients, which is a known determinant factor that may increase the prevalence of UTI [19,42], could be reasons for detecting lower prevalence of UTI in our study compared to the latter reports.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an increasing trend in ampicillinresistance (Aamodt et al 2015;Richey et al 2015). Contradict to other studies, Nitrofurantoin showed the second rank of the highest antibiotic resistance (92.31%) (Gardiner et al 2019;Zubair and Shah 2019). Table 2 showed majority isolates have resistant to 5 antibiotics (30.76%) and 2 isolates demonstrated resistant to 9 antibiotics (15.38%).…”
Section: Discussionmentioning
confidence: 71%